Dihydropyrimidine Dehydrogenase Levels in Colorectal Cancer Cells Treated with a Combination of Heat Shock Protein 90 Inhibitor and Oxaliplatin or Capecitabine - Mahshid Mohammadian; Shima Zeynali-Moghaddam; Mohammad Hassan Khadem Ansari; Yousef Rasmi; Anahita Fathi Azarbayjani; Fatemeh Kheradmand (Tabriz University of Medical Sciences, 2019)
Purpose: Dihydropyrimidine dehydrogenase (DPD) is the principal enzyme in the catabolism of fluoropyrimidine drugs including capecitabine. A recent report has suggested that oxaliplatin chemotherapy is associated with elevated DPD levels and chemoresistance pattern. As a newly developed chemotherapeutic agent, 17-allyloamino-17-demethoxy-geldanamycin (17-AAG) can be effective in combination therapy with oxaliplatin and capecitabine in colorectal cancer (CRC). DPD expression level can be a predictive factor in oxaliplatin and capecitabine-based chemotherapy. We evaluated DPD in mRNA and protein levels with new treatments: 17-AAG in combination with oxaliplatin and capecitabine in HT-29 and HCT-116 cell lines. Methods: Drug sensitivity was determined by the water-soluble tetrazolium-1 assay in a previous survey. Then, we evaluated the expression levels of DPD and its relationship with the chemotherapy response in capecitabine, oxaliplatin, and 17-AAG treated cases in single and combination cases in two panels of CRC cell lines. DPD gene and protein expression levels were determined by real-time polymerase chain reaction and western blotting assay, respectively. Results: DPD gene expression levels insignificantly increased in single-treated cases versus untreated controls in both cell lines versus controls. Then, the capecitabine and oxaliplatin were added in double combinations, where DPD gene and protein expression increased in combination cases compared to pre-chemotherapy and single drug treatments. Conclusion: The elevated levels of cytotoxicity in more effective combinations could be related to a different mechanism apart from DPD mediating effects or high DPD level in the remaining resistance cells (drug-insensitive cells), which should be investigated in subsequent studies.